2018
DOI: 10.1002/cam4.1431
|View full text |Cite
|
Sign up to set email alerts
|

Nutlin‐3a as a novel anticancer agent for adrenocortical carcinoma with CTNNB1 mutation

Abstract: Adrenocortical carcinoma (ACC) is a rare malignancy, and CTNNB1 is frequently mutated in ACC. Our study aims to screen for effective agents with antineoplastic activity against ACC with CTNNB1 mutation. In‐silico screening of the Genomics of Drug Sensitivity in Cancer (GDSC) database was conducted. Drug sensitivity in cells with CTNNB1 mutation was analyzed and further in vitro and in vivo studies were performed using the compound. Only one compound, Nutlin‐3a, an MDM2 inhibitor, was significantly sensitive in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…This is in line with the mechanism of action of SV40T, which is known to interfere with Rb and p53 pathways thus driving cell proliferation [20]. Finally, the susceptibility of cells to undergo p53-mediated apoptosis at non-permissive temperature was confirmed using nutlin-3a, a compound that selectively induces p53 by inhibiting its degradation via Mdm2 [45, 46], suggesting normal p53 activity and apoptosis regulation at non-permissive temperature.…”
Section: Discussionmentioning
confidence: 55%
“…This is in line with the mechanism of action of SV40T, which is known to interfere with Rb and p53 pathways thus driving cell proliferation [20]. Finally, the susceptibility of cells to undergo p53-mediated apoptosis at non-permissive temperature was confirmed using nutlin-3a, a compound that selectively induces p53 by inhibiting its degradation via Mdm2 [45, 46], suggesting normal p53 activity and apoptosis regulation at non-permissive temperature.…”
Section: Discussionmentioning
confidence: 55%
“…Nut is known to reduce cancer cell migration and invasion [ 80 , 81 ], and therefore it may be considered surprising that the treatment with the free drug was not able to reduce motility in our experimental conditions. However, the inhibitory effects of Nut on cell motility, which are known to be mediated by cytoskeletal rearrangements, are limited to p53 wild-type cells [ 79 ].…”
Section: Resultsmentioning
confidence: 91%
“…In this report, we have revisited the strategy of constructing PROTACs using the small molecule, idasanutlin -- a ligand with high affinity for the E3 ligase, MDM2 (37). Nutlins were initially developed to act as a pharmacological means to elevate expression of the tumor suppressor p53 and there have been numerous reports (4749) concerning the potential of nutlins as anti-cancer drugs/adjuvants. Our original study (25) indicated that nutlin-based PROTACs were limited in their ability to facilitate degradation: a PROTAC that recruited MDM2 to ubiquitinate the androgen receptor caused only limited target degradation at micromolar concentrations.…”
Section: Discussionmentioning
confidence: 99%